PVdF-HFP/Chitosan Polymer-blend Quasi-solid State Electrolyte for Dye-Sensitized Solar Cells Application - Wong , Theen Meng (IRC, 2016)
Dye-sensitized Solar Cells (DSSCs) has emerged to become one of the most promising alternatives to conventional solar cells. However, the long term stability and light-to-energy conversion efficiency of the electrolyte in DSSCs are the main challenges towards the commercial use of DSSCs. Liquid electrolytes in DSSCs have achieved high efficiency, but still suffer many disadvantages such as leakage, corrosion and high volatility. A novel gel-polymer electrolyte is introduced in this study by blending Poly(vinylidene fluoride-hexafluoropropylene) (PVdF-HFP) and Chitosan with ionic liquid in various compositions to encounter the problem. FTIR studies have been done to prove the interaction between the redox salt and polymer blend.The conversion efficiencies of DSSCs using the polymer gel electrolyte with the weight ratio of 3:1, 4:1, 5:1 and 6:1 (PVdF-HFP:Chitosan) are 1.207%, 0.566%, 0.461% and 1.231% respectively. It was found that the gel polymer electrolyte composed of 3:1 weight ratio of PVdF-HFP:Chitosan provides the highest ionic conductivity of 7.673×10-4 Scm-1.